The frequency of photosensitizing drug dispensings in Austria and Germany: a correlation with their photosensitizing potential based on published literature. (26th November 2019) - Hofmann, G.A.; Gradl, G.; Schulz, M.; Haidinger, G.; Tanew, A.; Weber, B.
Abstract: Background: Drug‐induced photosensitivity refers to the development of cutaneous adverse events due to interaction between a pharmaceutical compound and sunlight. Although photosensitivity is a very commonly listed side‐effect of systemic drugs, reliable data on its actual incidence are lacking so far. Objectives: A possible approach to evaluate the real‐life extent of drug‐induced photosensitivity would be an analysis of the frequency of exposure to a given photosensitizing drug combined with an indicator of its photosensitizing potential. This could serve as a basis for developing a pharmaceutical 'heatmap' of photosensitivity. Methods: The present study investigated the number of reimbursed dispensed packages of potentially photosensitizing drugs in Germany (DE) and Austria (AT) between 2010 and 2017 based on nationwide health insurance‐based databases. In addition, an indicator for the photosensitizing potential was established for each drug based on the number of reports on photosensitivity in the literature. Results: This analysis includes means of 632 826 944 (+/−14 894 918) drug dispensings per year in DE and 113 270 754 (+/−1 964 690) in AT. Out of these, the mean percentage of drugs that enlist photosensitivity as a potential side‐effect was 49.5% (±0.7) in DE and 48.2% (±1.2) in AT. When plotting the number of reimbursed dispensed packages vs. the number of reports on photosensitivity, two categories of drugs show high numbers for both parameters, that is diuretics and non‐steroidal anti‐inflammatory drugs (NSAIDs). Conclusions: Diuretics and NSAIDs appear to be responsible for the greatest part of exposure to photosensitizing drugs with potential implication on public health.